Biology of enlightenment - "Rao, Mukunda .(ed.)" (New Delhi, 2010)
In this book we meet with the modern sage, U.G. Krishnamurti, and listen to his penetrating voice describing life and reality as it is. What is body and what is mind? Is there a soul? Is there a beyond, a God? What is enlightenment? Is there a life after death? Never before have these questions been tackled with such simplicity, candour and clarity. In these unpublished early conversations with friends (1967-71), U.G.discusses in detail his search for the truth and how he underwent radical biological changes in 1967. Preferring to call it the natural state over enlightenment, he insists that whatever transformation he has undergone is within the structure of the human body and not in the mind at all. It is the natural state of being that sages like the Buddha, Jesus and, in modern times, Sri Ramana, stepped into. And U.G.never tires of pointing out that 'this is the way you, stripped of the machinations of thought, are also functioning.'
Keywords: Spirituality